New Challenges for Macroeconomic Policies: Economic Growth, Sustainable Development, Fiscal and Monetary Policies - Dufrénot, Gilles (Springer, 2024)
This book examines the economic policies that will underpin the evolution of growth in industrialised economies in coming decades. The change in focus of policymakers away from short-term regulation and policies towards problems of structural change is discussed in relation to the Taylor rule and Fisher relationship.